Polyalanine repeat polymorphism in RUNX2 is associated with site-specific fracture in post-menopausal females. - Nigel A Morrison; Alexandre S Stephens; Motomi Osato; Julie A Pasco; Nicolette Fozzard; Gary S Stein; Patsie Polly; Lyn R Griffiths; Geoff C Nicholson (PLoS ONE, 2013)
Runt related transcription factor 2 (RUNX2) is a key regulator of osteoblast differentiation. Several variations within the RUNX2 gene have been found to be associated with significant changes in BMD, which is a major risk factor for fracture. In this study we report that an 18 bp deletion within the polyalanine tract (17A>11A) of RUNX2 is significantly associated with fracture. Carriers of the 11A allele were found to be nearly twice as likely to have sustained fracture. Within the fracture category, there was a significant tendency of 11A carriers to present with fractures of distal radius and bones of intramembranous origin compared to bones of endochondral origin (p = 0.0001). In a population of random subjects, the 11A allele was associated with decreased levels of serum collagen cross links (CTx, p = 0.01), suggesting decreased bone turnover. The transactivation function of the 11A allele showed a minor quantitative decrease. Interestingly, we found no effect of the 11A allele on BMD at multiple skeletal sites. These findings suggest that the 11A allele is a biologically relevant polymorphism that influences serum CTx and confers enhanced fracture risk in a site-selective manner related to intramembranous bone ossification.